Jeszcze o nominantach w metodach porządkowania liniowego zbioru obiektów - Kowalewski, Grzegorz (About the nominants in to build aggregate variable describing complex phenomena else, 2006)
In order to build aggregate variable describing complex phenomena it is necessary the set of diagnostic variables is divided into three subsets: the subset of stimulants, the subset of destimulants and the subset of nominants. The nominants applies seldom in practical research although they take a stand often enough. In empirical research take often a stand the nominants, which can be called asymmetrical. Examples of the different nominants and manners of their transformations formulas on the stimulants are be presented in the article.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 519-528